Information literacy in 2015: International graduate business students' perceptions of information literacy skills compared to test-assessed skills. Issue 2 (2nd April 2016) - Michalak, Russell; Rysavy, Monica D. T.
ABSTRACT: In 2015, the information literacy (IL) team designed an instrument to determine international graduate business students' perceptions of their IL skills and their actual test-assessed IL skills. The purpose of this research was to compare international graduate students' perceptions of their IL skills versus their test-assessed competencies, with the aim of creating training modules to improve test-identified deficiencies. Results demonstrate that wide discrepancies exist between students' perceptions of their own skills and their actual skills on all six ILA-topic areas assessed by the internally developed test instruments, with students overestimating their abilities in all areas.